اختبار دور الوسيط لنية الشراء في العلاقة بين الصورة الذهنية للعلامة التجارية "SAMSUNG" وقرار الشراء - دراسة إمبريقية على عينة من الزبائن: Testing the role of the mediator for purchase intention in the relationship between the mental image of the brand "SAMSUNG" and the purchase decision - an empirical study on a sample of customers - - حميدي زقاي; رماس محمد أمين (Journal of North African Economies, 2025)
The study aimed to test the role of the mediator for the intention to purchase in the relationship between the mental image of the brand "SAMSUNG" and the purchase decision, through a field study on a sample of (87) customers from the state of Saida, to address this, a questionnaire was used that included (13) items, the results were analyzed using the statistical program (SPSS.V.22) in addition to the structural equations modeling program (Smart-Pls3). The study concluded that there is a significant effect of the mental image on both the intent to purchase and the purchase decision, the study also confirmed the existence of a significant effect of the mental image on the purchase decision with the presence of the intention to purchase as a mediating variable.